Preparation method of high-strength high-anti-stress beryllium copper alloy
Patent Information
- Application Number
- CN202611184801.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-23
AI Technical Summary
单纯依赖析出相的钉扎作用无法彻底消除可动位错
[0038](1)本发明采用无张力预时效与三次“冷轧+微张力时效”组合工艺制备的铍铜合金,抗拉强度可达900~1400 MPa,导电率达25%~60% IACS,200℃/1000h应力松弛率≤6%。与传统形变热处理工艺相比,本发明的铍铜合金强度提高5%~15%,导电率提高10%~30%,抗应力松弛性能提高60%以上。同时解决了现有铍铜合金中高铍含量带来的环境毒性风险、低铍合金强度不足及中温应力松弛失效的难题,实现了高强度、高导电率与优异抗应力松弛性能的协同优化。
Smart Images

Figure CN122959566A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of copper alloy preparation technology, specifically relating to a method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy. Background Technology
[0002] Beryllium copper alloys play an irreplaceable role in key fields such as electronic communications, aerospace, precision instruments, and relays due to their excellent high strength, high electrical / thermal conductivity, and wear resistance. Based on the beryllium content, beryllium copper alloys can be classified into low-beryllium high-conductivity type (Be 0.2~0.6 wt%), medium-beryllium high-strength type (Be 0.6~1.6 wt%), and high-beryllium high-strength type (Be 1.8~2.2 wt%). These alloys undergo solution treatment followed by aging treatment to precipitate nanoscale phases in the supersaturated solid solution, thereby achieving a balance between high strength and high conductivity. However, existing beryllium copper alloys commonly suffer from stress relaxation failure under medium-temperature service environments (100~300℃), meaning that the internal stress of the material gradually decreases over time under constant strain, directly affecting the reliability of long-life equipment such as precision electronic systems, connectors, springs, and relays. Therefore, improving stress relaxation resistance has become a core technical challenge that urgently needs to be solved in this field.
[0003] To promote the full precipitation of strengthening phases in beryllium copper alloys, a combined deformation heat treatment process is typically employed, involving multiple rounds of alternating "cold rolling + aging" after solution treatment. The basic logic of this process is that the high-density dislocations and deformation energy introduced by cold rolling provide numerous heterogeneous nucleation sites for the precipitates, significantly improving precipitation efficiency and enabling the alloy to achieve a high volume fraction of precipitates in a shorter time, ultimately resulting in excellent strength and conductivity matching. However, while improving precipitation efficiency, the combined deformation heat treatment process also introduces a serious side effect: the introduction of a large number of mobile dislocations. Specifically, each round of cold rolling injects a high density of geometrically necessary dislocations and statistically stored dislocations into the alloy matrix, a significant portion of which are mobile dislocations. Although subsequent aging treatment can fix some dislocations through the pinning effect of the precipitates, a considerable number of mobile dislocations are always retained due to the size and distribution of the precipitates.
[0004] It is particularly important to note that the effect of these numerous mobile dislocations on improving the mechanical properties of beryllium copper alloys is very limited. In precipitation-strengthened copper alloys, the main contribution to strength comes from precipitation strengthening caused by coherent strain between nanoscale precipitates and the matrix, as well as the Orowan bypass mechanism. The strengthening contribution of these mobile dislocations is usually far lower than that of fixed dislocations pinned by precipitates and grain boundaries, accounting for no more than 5% of the total strength. In contrast, the negative impact of mobile dislocations on conductivity and stress relaxation resistance is extremely prominent: on the one hand, lattice distortion around the dislocation core induces strong electron scattering, leading to a significant decrease in alloy conductivity. In alloys after traditional combined deformation heat treatment, high-density mobile dislocations severely deteriorate conductivity. On the other hand, under intermediate-temperature service conditions, thermal activation causes mobile dislocations to slip, climb, and annihilate each other, gradually releasing internal stress, which macroscopically manifests as stress relaxation. The higher the density of mobile dislocations, the more severe the stress relaxation. Traditional combined deformation heat treatment retains a large number of movable dislocations, causing the alloy to experience rapid stress decay in the early stages of service, making it difficult to meet the long-term reliability requirements of high-end equipment.
[0005] The fundamental reason why traditional processes struggle to address this problem lies in the inherent contradiction between improving precipitation efficiency (requiring high-density dislocations as nucleation sites) and reducing mobile dislocation density (reducing stress relaxation carriers). High-density dislocations are both a favorable factor for promoting precipitate nucleation and a detrimental factor for exacerbating stress relaxation and reducing conductivity. Simply relying on the pinning effect of precipitates cannot completely eliminate mobile dislocations. Once the precipitates coarsen or become unevenly distributed, their pinning effect weakens significantly. More critically, existing processes lack a mechanism for actively eliminating mobile dislocations; their annihilation often relies solely on spontaneous movement during service, leading to a decline in the alloy's stress relaxation performance. Therefore, effectively eliminating mobile dislocations with limited strength contribution while ensuring sufficient precipitation of nanoscale precipitates in beryllium copper alloys is crucial for preparing high-strength, high-stress-relaxation-resistant beryllium copper alloys. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing high-strength, high-stress-relaxation-resistant beryllium copper alloys. This invention utilizes a pre-aging process combined with a cyclic combination of three cold rolling-micro-tension aging processes to significantly improve the alloy's stress relaxation resistance, strength, and conductivity while maintaining its original composition. The preparation method of this invention is applicable to low-beryllium, medium-beryllium, high-beryllium, and multi-component beryllium copper alloys. Through flexible adjustment of process parameters, the synergistic optimization of the properties of beryllium copper alloys with different compositions can be achieved.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] The present invention also provides a method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy, wherein the beryllium copper alloy solution billet is pre-aged, and the pre-aged billet is sequentially subjected to a first cold rolling, a first micro-tension aging, a second cold rolling, a second micro-tension aging, a third cold rolling, and a third micro-tension aging.
[0009] During the first micro-tension aging process, a constant tensile stress F1 is applied along the rolling direction to the alloy plate obtained by the first cold rolling, while the temperature is raised to K1 and held at that temperature.
[0010] During the secondary micro-tension aging process, a constant tensile stress F2 is applied along the rolling direction to the alloy plate obtained by the secondary cold rolling, while the temperature is raised to K2 and held at that temperature.
[0011] During the three-stage micro-tension aging process, a constant tensile stress F3 is applied along the rolling direction to the alloy plate obtained by the three-stage cold rolling, while the temperature is raised to K3 and held at that temperature.
[0012] Where F1>F2>F3, K1>K2>K3.
[0013] In this invention, micro-tension aging refers to applying a certain tensile stress to the plate during the aging heat treatment process. In this invention, the tensile stress direction of micro-tension aging is always along the rolling direction of the plate and remains constant during the heat preservation period.
[0014] The preparation method of this invention first pre-ages the beryllium copper alloy solution billet to promote the uniform distribution of nanoscale precipitate nuclei, suppress the formation of discontinuous precipitates (γ phase), refine the size of precipitates, and eliminate local stress concentrations generated during hot rolling or solution treatment, thereby improving the uniformity of the alloy structure. Subsequently, a three-stage combination process of cold rolling-micro-tension aging is performed. During micro-tension aging, on the one hand, the nucleation energy barrier of precipitates can be significantly reduced by the applied stress field, generating stress-induced precipitation effect, promoting the full precipitation and refinement of nanoscale strengthening phases (such as γ'' phase and γ' phase), thereby greatly improving the contribution of precipitation strengthening. On the other hand, the applied stress actively drives the movable dislocations introduced by cold rolling to slip, climb, and annihilate each other, reducing the movable dislocation density. Moreover, experiments have shown that during micro-tension aging, the contribution of movable dislocations to strength usually does not exceed 5% of the total strength, and the strength improvement effect brought by stress-induced precipitation is far greater than the weak strengthening contribution lost by the elimination of movable dislocations. Therefore, micro-tension aging significantly improves the net strength of the alloy. At the same time, the substantial reduction in the density of movable dislocations effectively reduces electron scattering and stress relaxation carriers, thereby simultaneously improving conductivity and stress relaxation resistance.
[0015] Experimental findings indicate that pre-aging before the cold rolling-micro-tension aging cycle is crucial. Pre-aging precipitates fine, dispersed nanoscale strengthening phases in the matrix. These pre-precipitated phases act as high-density dislocation pinning sites during subsequent cold rolling, significantly increasing the proportion of pinned fixed dislocations among the numerous dislocations introduced by cold rolling, thereby reducing the proportion of movable dislocations in the total dislocations. This approach reduces the number of movable dislocations that need to be eliminated during subsequent micro-tension aging and enhances the auxiliary role of fixed dislocations in precipitate nucleation, laying a structural foundation for the synergistic optimization of strength and stress relaxation resistance during subsequent micro-tension aging. Subsequently, main aging and other steps further promote uniform nucleation and controllable growth of the precipitates, preventing the formation of coarse precipitates and ensuring that nanoscale precipitates formed by elements such as Be, Ni, and Co, such as BeCu, NiBe, and CoBe, are distributed in a fine and continuous manner in the matrix, while simultaneously reducing the movable dislocation density, thus improving the overall performance of the alloy.
[0016] Furthermore, in this invention, the temperature and pressure are gradually reduced during the three aging processes. The stepped cooling mode is a graded aging strategy that achieves precise control over the evolution of precipitates, dislocation behavior, and microstructure stability in stages. Before the first aging, the alloy has a high dislocation density and sufficient deformation energy after large deformation cold rolling. Using a higher temperature K1 can fully activate the diffusion of solute atoms such as Be, Ni, and Co. Combined with the induction effect of applied stress, a large number of uniform and fine nano-precipitate nuclei are quickly formed in the matrix, avoiding the problems of insufficient nucleation and excessively long precipitation cycle in a single low-temperature aging. The subsequent second and third aging processes gradually reduce the temperature, which can control the slow growth of precipitates and maintain the coherent / semi-coherent interface state on the basis of a large number of precipitate nuclei. This suppresses the coarsening of precipitates and Ostwald ripening, ensuring that the precipitates always maintain nanoscale size and dispersed distribution characteristics to maximize the precipitation strengthening effect. At the same time, it avoids the discontinuous precipitation of coarse γ phases at grain boundaries caused by prolonged high-temperature residence, eliminating the hidden danger of grain boundary weakening. In this stepped temperature system, the high-temperature K1 stage mainly drives the slip and climb of large-scale mobile dislocations and unstable dislocations in the dislocation cell wall, rapidly annihilating most of the mobile dislocations in the high dislocation density region, while promoting dislocation rearrangement to form a more stable subcrystalline structure. In the intermediate-temperature K2 and low-temperature K3 stages, the thermal activation energy is gradually reduced, driving only the remaining short-range mobile dislocations and lattice dislocations to slowly annihilate, without shaking the fixed dislocations pinned by the precipitated phase. This ensures that the density of mobile dislocations is reduced to the minimum to reduce the stress relaxation carrier, while maximizing the strengthening contribution of fixed dislocations, achieving precise control of removing harmful dislocations and retaining beneficial dislocations. Furthermore, the stepped cooling aging process is equivalent to performing multiple rounds of annealing stabilization treatment on the precipitates and dislocation structures. Finally, the third low-temperature aging process can fully eliminate the internal stress remaining from the previous process, enabling the precipitate-matrix interface to reach a low-energy steady state. This reduces the coarsening of precipitates and dislocation recovery behavior driven by interface energy during service, significantly reducing the microstructure evolution rate of the alloy during long-term service at medium temperatures, making the stress relaxation rate more gradual, and greatly improving long-term reliability.
[0017] The gradual reduction of tensile stress matches the changes in the microstructure of the alloy after multiple cold rolling-aging cycles, achieving an optimal balance between stress-induced precipitation and dislocation control. After the first cold rolling, the alloy has the highest dislocation density and a large proportion of movable dislocations. The high F1 provides sufficient shear stress driving force, prompting movable dislocations to slip, climb, and annihilate each other, while strengthening the stress-induced precipitation effect and accelerating the segregation and nucleation of solute atoms at dislocations. After the preceding aging, a large number of movable dislocations have been eliminated and some dislocations have been pinned by the precipitates. The number of newly introduced movable dislocations introduced by subsequent cold rolling cycles decreases gradually. If high stress is maintained at this time, it will cause the pinned fixed dislocations to detach and reactivate as movable dislocations, or even cause dislocation proliferation, which will deteriorate the stress relaxation resistance. The gradual reduction of stress can accurately match the decreasing level of movable dislocations in each cycle, ensuring the dislocation elimination effect without destroying the already formed stable dislocation-precipitate structure. Furthermore, beryllium copper alloys, especially high-beryllium systems, have limited plasticity. After multiple rounds of cold rolling and aging cycles, the degree of work hardening increases with each cycle, and the high tensile stress is prone to stress concentration at the edges and grain boundaries of the sheet, leading to defects such as microcracks, edge cracks, and delamination. The stress can be gradually reduced as the degree of alloy hardening increases, which can reduce the applied load, avoid stress accumulation damage, reduce the residual stress level of the final product, and improve the dimensional accuracy and processing yield of subsequent stamping and precision etching.
[0018] In a preferred embodiment, the process of obtaining the beryllium copper alloy solution billet is as follows: homogenizing the beryllium copper alloy ingot to obtain a homogenized billet, hot-rolling the homogenized billet to obtain a hot-rolled billet, and then performing a solution treatment on the hot-rolled billet to obtain the final product.
[0019] In this invention, the beryllium copper alloy ingot can be obtained by conventional melting methods. For example, the components of the beryllium copper alloy are prepared according to the design ratio, and the copper source, copper-beryllium master alloy, and other alloy element master alloys are placed in a vacuum melting furnace. The vacuum is evacuated to a vacuum degree ≤5×10⁻³ Pa, heated to the specified melt temperature and held for a period of time to obtain the alloy melt, which is then cast.
[0020] In a further preferred embodiment, the hot rolling temperature is 750–970°C. Before hot rolling, the alloy is held at 750–970°C for 1–3 hours, and between passes, it is held at 750–970°C for 15–30 minutes. After hot rolling, it is water-cooled to room temperature. In this invention, preheating and holding before hot rolling, as well as holding between passes, ensure that hot rolling is performed within the specified temperature range. If the temperature is too low, coarse β-phase will form in the alloy during hot working, severely deteriorating the alloy's properties; if the temperature is too high, it can easily cause coarse grains or even overheating.
[0021] In a further preferred embodiment, the hot rolling is performed in three passes, with a total deformation of 70-85%, and the deformation per pass being 35-40%, 20-35%, and 15-30% of the total deformation, respectively. In this invention, the appropriately decreasing deformation results in superior material performance.
[0022] In a further preferred embodiment, the solution treatment is performed under a protective atmosphere, at a temperature of 780–950°C, for a duration of 0.5–4 hours, and after the solution treatment, the sample is water-quenched to room temperature to obtain a solution-treated compact. By controlling the solution treatment temperature within the above range, both sufficient solution treatment and prevention of grain growth can be ensured.
[0023] Further optimization revealed that when the beryllium mass fraction in the beryllium-copper alloy is ≤0.6 wt%, the solution treatment temperature is 880–950℃, and the solution treatment time is 0.5–4 h; when the beryllium mass fraction in the beryllium-copper alloy is >0.6 wt%, the solution treatment temperature is 780–870℃, and the solution treatment time is 0.5–3 h. Experiments showed that, based on the Be content, controlling the solution treatment temperature within the above range resulted in the optimal performance of the beryllium-copper alloy.
[0024] In a preferred embodiment, the pre-aging is carried out under a protective atmosphere, the pre-aging temperature is 280~450℃, the pre-aging time is 0.5~3h, and after the pre-aging is completed, it is cooled to room temperature with water.
[0025] Further preferred, when the mass fraction of beryllium in the beryllium copper alloy is ≤0.6 wt%, the pre-aging temperature is 400~450℃ and the pre-aging time is 0.5~2h; when the mass fraction of beryllium in the beryllium copper alloy is >0.6 wt%, the pre-aging temperature is 280~350℃ and the pre-aging time is 0.5~3h.
[0026] In a preferred embodiment, the total deformation of the single cold rolling is 50% to 80%, and the single cold rolling is carried out in three passes, with the deformation amounts of each pass being 40% to 50%, 20% to 35%, and 15% to 30% of the total deformation, respectively. The deformation amount decreases progressively with each pass to facilitate uniform microstructure and prevent cracking.
[0027] In a preferred embodiment, the total deformation of the secondary cold rolling is 30% to 60%, and the secondary cold rolling is carried out in three passes, with the deformation amounts of each pass being 40% to 45%, 25% to 35%, and 20% to 35% of the total deformation, respectively.
[0028] In a preferred embodiment, the total deformation of the three cold rolling processes is 30% to 60%, and the three cold rolling processes are carried out in three passes, with the deformation amounts of each pass being 40% to 45%, 25% to 35%, and 20% to 35% of the total deformation, respectively.
[0029] In a preferred embodiment, F1 is 120-200 MPa, preferably 120-150 MPa; F1 is 20-50 MPa greater than F2, preferably 20-30 MPa, and F2 is 20-50 MPa greater than F3, preferably 20-40 MPa.
[0030] In this invention, the stress applied during micro-tension aging is controlled within the above-mentioned range for optimal performance. This ensures that the precipitated phase is finely dispersed and that mobile dislocations are fully eliminated. If the stress is too low, the stress-induced precipitation effect is not obvious, the mobile dislocations are not fully eliminated, and it is difficult to effectively improve the stress relaxation resistance. If the stress is too high, the precipitated phase will be too coarse, and the fixed dislocations that were originally pinned may also be annihilated, which will instead cause a decrease in strength and stress relaxation resistance.
[0031] In this invention, the stress difference between adjacent stages (F1-F2, F2-F3) needs to be controlled within a reasonable range. If the difference is too small (<20MPa), the functional distinction between the three aging cycles will disappear, approximating constant stress aging. This cannot match the progressively changing dislocation density and precipitation state, leading to insufficient nucleation driving force in the early stages and an increased risk of dislocation depinning in the later stages, limiting the improvement in stress relaxation resistance. Furthermore, it prevents the gradual release of internal stress, resulting in residual stress accumulation after multiple cycles. This makes the finished sheet prone to warping and poor shape, leading to poor dimensional stability during subsequent precision machining. Simultaneously, the evolution of precipitates lacks hierarchy, easily resulting in wide size distribution and localized coarsening, affecting strength and conductivity. The synergistic optimization effect of electrical conductivity decreases; while excessively large differences (>50MPa) will cause excessive stress abrupt changes, resulting in additional thermal stress and structural stress inside the plate. In high beryllium alloys, grain boundary slip and microcrack initiation are easily induced, the processing yield decreases significantly, and the subsequent time stress level drops sharply, which cannot effectively drive the annihilation of the remaining mobile dislocations. The dislocation elimination is incomplete, and the mobile dislocations continue to move during service. The stress relaxation rate increases significantly, which will also lead to the disjointed evolution of precipitates. The large number of precipitate nuclei formed under the first high stress lack sufficient solute atom diffusion driving force due to the subsequent sharp drop in stress. The precipitate growth is uneven, the strengthening effect fluctuates greatly, and the batch performance stability is poor.
[0032] In a preferred embodiment, K1 is 280~450℃, K1 is 5~50℃ higher than K2, preferably 10~30℃; K2 is 5~50℃ higher than K3, preferably 20~45℃.
[0033] In this invention, the temperature difference between adjacent stages (K1-K2, K2-K3) is also crucial to the control effect of graded aging. If the difference is too small (<5℃), the graded aging effect will fail, approximating isothermal aging. This not only results in insufficient nuclei of precipitated phases and uncontrolled growth, but also leads to a wide size distribution, an increased proportion of coarse precipitates, a decreased proportion of coherent interfaces, and a weakened precipitation strengthening effect. Furthermore, it indirectly prolongs the high-temperature equivalent residence time, causing excessive recovery, climb, or even annihilation of fixed dislocations, resulting in a loss of dislocation strengthening contribution and an irreversible decrease in alloy strength. At the same time, the risk of discontinuous precipitation at grain boundaries increases, and solute atoms tend to agglomerate at grain boundaries to form a continuous network of γ-rays. The phase difference deteriorates the grain boundary bonding strength, making it prone to grain boundary slip during service and accelerating the stress relaxation rate. However, if the difference is too large (>50℃), it will cause a sharp drop in the subsequent aging temperature, resulting in a severe lack of driving force for solute atom diffusion. The precipitation of the phase is hindered, and the volume fraction cannot reach the peak value. This not only loses the precipitation strengthening effect, but also reduces the conductivity due to the increased electron scattering caused by too many solid solution atoms in the matrix. Furthermore, the activation energy for climb and slip of mobile dislocations is insufficient at low temperatures, and the dislocation annihilation reaction is incomplete. A large number of mobile dislocations remain in the matrix, and dislocation movement continues during service, increasing the stress relaxation rate. In addition, the sudden change in the microstructure between two aging cycles can cause a sudden change in the mismatch degree of the precipitate phase-matrix interface, which can easily lead to the proliferation of interface dislocations and introduce new mobile dislocations, thus offsetting the effect of previous dislocation elimination.
[0034] Further optimization is achieved when the mass fraction of beryllium in the beryllium-copper alloy is ≤0.6 wt%, K1 is 400~450℃, and the holding time at K1 is 0.5~2h; when the mass fraction of beryllium in the beryllium-copper alloy is >0.6 wt%, K1 is 280~350℃, and the holding time at K1 is 0.5~3h.
[0035] Furthermore, the micro-tension aging process is as follows: Figure 1 As shown: The sample is placed in a tube furnace and fixed with clamps on both sides. Tensile force is applied and adjusted by a tensile testing system (not shown in the figure), and aging is carried out as the furnace temperature rises. The tube furnace and tensile testing system are existing technologies and will not be described in detail.
[0036] The beryllium copper alloy prepared by the above method has a tensile strength of 900~1700 MPa, an electrical conductivity of 25%~60% IACS, a stress relaxation rate of ≤6% at 200℃ / 1000h, and a significant reduction in discontinuous precipitates at grain boundaries. Its comprehensive performance is superior to that of traditional deformation heat treatment processes.
[0037] Beneficial effects
[0038] (1) The beryllium copper alloy prepared by the present invention using a combination of tensionless pre-aging and three-stage "cold rolling + micro-tension aging" process has a tensile strength of 900-1400 MPa, a conductivity of 25%-60% IACS, and a stress relaxation rate of ≤6% at 200℃ / 1000h. Compared with the traditional deformation heat treatment process, the beryllium copper alloy of the present invention has a strength increase of 5%-15%, a conductivity increase of 10%-30%, and a stress relaxation resistance increase of more than 60%. At the same time, it solves the problems of environmental toxicity risks caused by high beryllium content in existing beryllium copper alloys, insufficient strength of low beryllium alloys, and medium-temperature stress relaxation failure, and achieves synergistic optimization of high strength, high conductivity, and excellent stress relaxation resistance.
[0039] (2) This invention replaces traditional tensionless aging with micro-tension aging. Under the premise of ensuring that the alloy performance meets the service requirements and stability, the beryllium content can be reduced by 0.2 to 0.5 wt%, thereby reducing production costs and environmental health risks. The overall manufacturing cost can be reduced by about 20% to 40%.
[0040] (3) The preparation method of the present invention adopts multi-pass cold rolling with decreasing deformation and step-type micro-tension aging, which effectively avoids defects such as cracking and peeling during the processing. The finished product rate is ≥95%, and the subsequent stamping, etching, welding and other processing performance is good, which is suitable for the manufacturing of complex precision parts.
[0041] (4) The method of the present invention has strong universality and is applicable to various beryllium copper alloys: it has a significant performance improvement effect on low beryllium (Be 0.2~0.6 wt%), medium beryllium (Be 0.6~1.6 wt%), high beryllium (Be 1.6~2.2 wt%) and multi-element beryllium copper alloys (such as Cu-Be-Ni-Co-Mg, etc.). Only by adjusting the specific process parameters (temperature, time, tensile stress value) according to the alloy composition can excellent comprehensive performance be obtained.
[0042] (5) The beryllium copper alloy of the present invention can meet the stringent requirements of high-end fields such as aerospace precision relays, 5G high-frequency and high-speed connectors, high-reliability defense electronic systems and ultra-precision instruments for the comprehensive performance of materials, and provides a new material option with high cost performance for high-end electronics, aerospace and precision manufacturing fields. Attached Figure Description
[0043] Figure 1 This is a schematic diagram of the micro-tension aging process.
[0044] Figure 2 The TEM microstructure of the sample in Example 1.
[0045] Figure 3 The TEM microstructure of the sample in Comparative Example 1 is shown. Detailed Implementation
[0046] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not have a limiting effect on the scope of protection.
[0047] In the following embodiments, the micro-tension aging process is as follows: Figure 1 As shown, the sample is placed in the furnace and fixed with clamps on both sides. The tensile force is applied and adjusted by the tensile system, and the sample is aged as the furnace temperature rises.
[0048] Example 1
[0049] The high-strength, high-stress-relaxation-resistant Cu-Be-Ni-Co-Mg alloy and its preparation method are described in this embodiment:
[0050] Composition: Be 1.6 wt%, Ni 0.2 wt%, Co 0.3 wt%, Si 0.1 wt%, balance Cu.
[0051] Process flow:
[0052] (1) Smelting: Place the electrolytic copper plate and other intermediate alloy raw materials in a vacuum smelting furnace and evacuate to a vacuum degree ≤5×10 -3 Pa is heated to 1200℃ for smelting. After all the alloy raw materials have melted, the melt is poured into a water-cooled mold to cool and obtain an alloy ingot.
[0053] (2) Homogenization treatment: The alloy ingot is kept at 850℃ for 6 hours for homogenization treatment, argon gas is introduced for protection, and then water is cooled after treatment.
[0054] (3) Hot rolling: The homogenized alloy ingot is held at 850℃ for 1 hour and then hot rolled. The total deformation of hot rolling is 80%. It is rolled in three passes with deformation amounts of 40%, 35% and 25% of the total deformation, respectively. The passes are held at 850℃ for 20 minutes between passes. After hot rolling, it is water cooled to obtain a hot rolled billet.
[0055] (4) Solution treatment: The hot-rolled billet is kept at 850℃ for 1 hour and then quenched in water to room temperature to obtain a solution-treated billet.
[0056] (5) Tensionless pre-aging: The solution-treated billet is kept at 280°C for 30 minutes in a protective atmosphere furnace without applying any external force, and then cooled with water.
[0057] (6) First cold rolling: The alloy plate processed in step (5) is cold rolled at room temperature with a total deformation of 75%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a first-pass cold-rolled plate.
[0058] (7) First micro-tension aging: The cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 150MPa is applied along the rolling direction. It is kept at 325℃ for 2 hours in a protective atmosphere furnace to maintain constant tension. After the end, the tension is removed and the plate is water-cooled.
[0059] (8) Second cold rolling: The alloy plate processed in step (7) is cold rolled at room temperature with a total deformation of 50%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a second cold-rolled plate.
[0060] (9) Second micro-tension aging: The second cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 120MPa is applied along the rolling direction. It is kept at 300℃ for 1.5h in a protective atmosphere furnace to maintain constant tension, and then water-cooled after completion.
[0061] (10) Third cold rolling: The alloy plate processed in step (9) is cold rolled at room temperature with a total deformation of 50%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a three-stage cold-rolled plate.
[0062] (11) Third micro-tension aging: The three-time cold-rolled plate is placed into a micro-tension fixture, and a constant tensile stress of 80 MPa is applied along the rolling direction. It is then held at 280°C for 4 hours in a protective atmosphere furnace while maintaining constant tension. After the process, it is water-cooled to obtain the final alloy.
[0063] Appendix Figure 2 The TEM microstructure of the sample in Example 1 shows that a large number of dispersed second-phase particles have formed in the alloy. These particles significantly improve the mechanical properties and stress relaxation resistance of the alloy.
[0064] The resulting alloy has the following properties: tensile strength of 1630 MPa, electrical conductivity of 30.8% IACS, and stress relaxation rate of 4.8% at 200℃ / 1000h.
[0065] Example 2
[0066] The difference between this embodiment and Embodiment 1 lies in the composition and some process parameters.
[0067] (1) Composition: Be 1.2 wt%, Ni 0.5 wt%, Co 0.2 wt%, Mg 0.1 wt%, balance Cu.
[0068] (2) Solution treatment: The hot-rolled billet is kept at 870℃ for 1 hour and then quenched in water to room temperature to obtain a solution-treated billet.
[0069] (3) First micro-tension aging: The cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 120MPa is applied along the rolling direction. It is kept at 325℃ for 2 hours in a protective atmosphere furnace to maintain constant tension. After the end, the tension is removed and the plate is water-cooled.
[0070] (4) Second micro-tension aging: The second cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 100MPa is applied along the rolling direction. It is kept at 300℃ for 1.5h in a protective atmosphere furnace to maintain constant tension, and then water-cooled after completion.
[0071] (5) Third micro-tension aging: The three-time cold-rolled plate is placed into a micro-tension fixture, and a constant tensile stress of 60 MPa is applied along the rolling direction. It is then held at 280°C for 4 hours in a protective atmosphere furnace while maintaining constant tension. After the process, it is water-cooled to obtain the final alloy.
[0072] The resulting alloy has the following properties: tensile strength of 1370 MPa, electrical conductivity of 38.4% IACS, and stress relaxation rate of 3.7% at 200℃ / 1000h.
[0073] Example 3
[0074] The difference between this embodiment and Embodiment 1 lies in the composition and some process parameters.
[0075] (1) Composition: Be 0.9 wt%, Ni 0.5 wt%, Co 0.3 wt%, Mg 0.15 wt%, balance Cu.
[0076] (2) Homogenization treatment: The alloy ingot is kept at 900℃ for 6 hours for homogenization treatment, argon gas is introduced for protection, and then water is cooled after treatment.
[0077] (3) Solution treatment: The hot-rolled billet is kept at 850℃ for 1 hour and then quenched in water to room temperature to obtain a solution-treated billet.
[0078] (4) Tensionless pre-aging: The solution-treated billet is kept at 260°C for 60 minutes in a protective atmosphere furnace without applying any external force, and then cooled with water.
[0079] (5) First micro-tension aging: The cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 150MPa is applied along the rolling direction. It is kept at 320℃ for 1h in a protective atmosphere furnace to maintain constant tension. After the end, the tension is removed and the plate is water-cooled.
[0080] (6) Second micro-tension aging: The second cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 120MPa is applied along the rolling direction. It is kept at 290℃ for 2 hours in a protective atmosphere furnace to maintain constant tension, and then water-cooled after completion.
[0081] (7) Third micro-tension aging: The three-time cold-rolled plate is placed into a micro-tension fixture, and a constant tensile stress of 80 MPa is applied along the rolling direction. It is then held at 270°C for 3 hours in a protective atmosphere furnace while maintaining constant tension. After the process, it is water-cooled to obtain the final alloy.
[0082] The resulting alloy has the following properties: tensile strength of 1280 MPa, electrical conductivity of 40.3% IACS, and stress relaxation rate of 5.2% at 200℃ / 1000h.
[0083] Example 4
[0084] The difference between this embodiment and Embodiment 1 lies in the different components.
[0085] (1) Composition: Be 2.0 wt%, Ni 0.3 wt%, Zr 0.2 wt%, balance Cu.
[0086] The resulting alloy has the following properties: tensile strength of 1767 MPa, electrical conductivity of 27.8% IACS, and stress relaxation rate of 5.8% at 200℃ / 1000h.
[0087] Example 5
[0088] Composition: Be 0.6 wt%, Ni 2.1 wt%, balance Cu.
[0089] Process flow:
[0090] (1) Smelting: Place the electrolytic copper plate and other intermediate alloy raw materials in a vacuum smelting furnace and evacuate to a vacuum degree ≤5×10 -3 Pa is heated to 1200℃ for smelting. After all the alloy raw materials have melted, the melt is poured into a water-cooled mold to cool and obtain an alloy ingot.
[0091] (2) Homogenization treatment: The alloy ingot is kept at 950℃ for 6 hours for homogenization treatment, argon gas is introduced for protection, and then water is cooled after treatment.
[0092] (3) Hot rolling: The homogenized alloy ingot is held at 950℃ for 1 hour and then hot rolled. The total deformation of hot rolling is 80%. It is rolled in three passes with deformation amounts of 40%, 30% and 30% of the total deformation, respectively. The passes are held at 950℃ for 20 minutes between passes. After hot rolling, it is water cooled to obtain a hot rolled billet.
[0093] (4) Solution treatment: The hot-rolled billet is kept at 950℃ for 1 hour and then quenched in water to room temperature to obtain a solution-treated billet.
[0094] (5) Tensionless pre-aging: The solution-treated billet is kept at 425°C for 30 minutes in a protective atmosphere furnace without applying any external force, and then cooled with water.
[0095] (6) First cold rolling: The alloy plate processed in step (5) is cold rolled at room temperature with a total deformation of 70%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a first-pass cold-rolled plate.
[0096] (7) First micro-tension aging: The cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 150MPa is applied along the rolling direction. It is kept at 450℃ for 30min in a protective atmosphere furnace to maintain constant tension. After the end, the tension is removed and the plate is water-cooled.
[0097] (8) Second cold rolling: The alloy plate processed in step (7) is cold rolled at room temperature with a total deformation of 50%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a second cold-rolled plate.
[0098] (9) Second micro-tension aging: The second cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 120MPa is applied along the rolling direction. It is kept at 425℃ for 30min in a protective atmosphere furnace to maintain constant tension. After the end, it is water-cooled.
[0099] (10) Third cold rolling: The alloy plate processed in step (9) is cold rolled at room temperature with a total deformation of 50%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a three-stage cold-rolled plate.
[0100] (11) Third micro-tension aging: The three-time cold-rolled plate is placed into a micro-tension fixture, and a constant tensile stress of 80 MPa is applied along the rolling direction. It is then held at 380°C for 1 hour in a protective atmosphere furnace while maintaining constant tension. After the process, it is water-cooled to obtain the final alloy.
[0101] The resulting alloy has the following properties: tensile strength of 1130 MPa, electrical conductivity of 62.1% IACS, and stress relaxation rate of 4.2% at 200℃ / 1000h.
[0102] Example 6
[0103] The difference between this embodiment and Embodiment 5 lies in the different components and the different micro-tension aging process.
[0104] (1) Composition: Be 0.3 wt%, Co 1.3 wt%, balance Cu.
[0105] The resulting alloy has the following properties: tensile strength of 1767 MPa, electrical conductivity of 27.8% IACS, and stress relaxation rate of 5.8% at 200℃ / 1000h.
[0106] (2) First micro-tension aging: The cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 120MPa is applied along the rolling direction. It is kept at 450℃ for 45min in a protective atmosphere furnace to maintain constant tension. After the end, the tension is removed and the plate is water-cooled.
[0107] (3) Second micro-tension aging: The second cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 100MPa is applied along the rolling direction. It is kept at 440℃ for 30min in a protective atmosphere furnace to maintain constant tension. After the end, it is water-cooled.
[0108] (11) Third micro-tension aging: The three-time cold-rolled plate is placed into a micro-tension fixture, and a constant tensile stress of 80 MPa is applied along the rolling direction. It is then held at 400℃ for 1 h in a protective atmosphere furnace while maintaining constant tension. After the process, it is water-cooled to obtain the final alloy.
[0109] The resulting alloy has the following properties: tensile strength of 1030 MPa, electrical conductivity of 67.1% IACS, and stress relaxation rate of 5.2% at 200℃ / 1000h.
[0110] Example 7
[0111] The difference between this embodiment and Embodiment 5 lies in the cold rolling process.
[0112] (1) First cold rolling: The alloy plate processed in step (5) is cold rolled at room temperature with a total deformation of 90%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a first-pass cold-rolled plate.
[0113] (2) Second cold rolling: The alloy plate processed in step (7) is cold rolled at room temperature with a total deformation of 60%. It is rolled in three passes with the deformation amounts of each pass being 40%, 30%, and 30% of the total deformation, respectively, to obtain a second cold-rolled plate.
[0114] (3) Third cold rolling: The alloy plate processed in step (9) is cold rolled at room temperature with a total deformation of 40%. It is rolled in three passes with the deformation amounts of the passes being 40%, 30%, and 30% of the total deformation, respectively, to obtain a three-stage cold-rolled plate.
[0115] The resulting alloy has the following properties: tensile strength of 1050 MPa, electrical conductivity of 63.2% IACS, and stress relaxation rate of 4.2% at 200℃ / 1000h.
[0116] Comparative Example 1
[0117] The difference between Comparative Example 1 and Example 1 is that all the micro-tension aging was replaced with tension-free conventional aging.
[0118] Appendix Figure 3The TEM microstructure of the sample in Comparative Example 1 shows a significantly lower amount of precipitated phases in the alloy compared to Example 1 (see attached image). Figure 2 )
[0119] The resulting alloy has the following properties: tensile strength of 1340 MPa, electrical conductivity of 28.3% IACS, and stress relaxation rate of 32.2% at 200℃ / 1000h.
[0120] Comparative Example 2
[0121] The only difference between this comparative example and Example 1 is that the tensile stress during the first micro-tension aging exceeds the scope of this invention, while the other process parameters are completely identical.
[0122] First micro-tension aging: The cold-rolled sheet was placed in a micro-tension fixture, and a constant tensile stress of 300 MPa was applied along the rolling direction. It was then held at 325°C for 2 hours in a protective atmosphere furnace while maintaining constant tension. After the aging process, the tension was removed and the sheet was water-cooled. The tensile stress, temperature, and time for the second and third micro-tension aging processes were the same as in Example 1. The resulting alloy properties were: tensile strength 840 MPa, electrical conductivity 29.7% IACS, and stress relaxation rate of 40.7% at 200°C for 1000 hours.
[0123] Comparative Example 3
[0124] The difference between Comparative Example 3 and Example 4 lies in the different tensions during micro-tension aging.
[0125] (1) First micro-tension aging: The cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 300MPa is applied along the rolling direction. It is kept at 325℃ for 2 hours in a protective atmosphere furnace to maintain constant tension. After the end, the tension is removed and the plate is water-cooled.
[0126] (2) Second micro-tension aging: The second cold-rolled plate is placed into the micro-tension fixture, and a constant tensile stress of 200MPa is applied along the rolling direction. It is kept at 300℃ for 1.5h in a protective atmosphere furnace to maintain constant tension, and then water-cooled after completion.
[0127] (3) Third micro-tension aging: The three-time cold-rolled plate is placed into a micro-tension fixture, and a constant tensile stress of 200 MPa is applied along the rolling direction. It is then held at 280°C for 4 hours in a protective atmosphere furnace while maintaining constant tension. After the process, it is water-cooled to obtain the final alloy.
[0128] The resulting alloy has the following properties: tensile strength of 840 MPa, electrical conductivity of 29.7% IACS, and stress relaxation rate of 40.7% at 200℃ for 1000h.
[0129] The resulting alloy has the following properties: tensile strength of 1140 MPa, electrical conductivity of 21.7% IACS, and stress relaxation rate of 42.5% at 200℃ / 1000h.
[0130] Comparative Example 4
[0131] The difference between Comparative Example 4 and Example 1 is that all the micro-tension aging was changed to tension-free conventional aging.
[0132] The resulting alloy has the following properties: tensile strength of 1335 MPa, electrical conductivity of 21.7% IACS, and stress relaxation rate of 42.9% at 200℃ / 1000h.
[0133] Comparative Example 5
[0134] The only difference between this comparative example and Example 5 is that the stress-decreasing design is omitted, and constant tensile stress is used for all three micro-tension aging processes; all other process parameters are completely identical. A constant tensile stress of 150 MPa is applied along the rolling direction for the first, second, and third micro-tension aging processes, and the corresponding aging temperature and holding time remain consistent with Example 5. The resulting alloy properties are: tensile strength 730 MPa, electrical conductivity 55.1% IACS, and stress relaxation rate of 53.2% at 200℃ / 1000h.
[0135] Comparative Example 6
[0136] The difference between Comparative Example 1 and Example 1 is that all the micro-tension aging was changed to tension-free conventional aging. The resulting alloy properties are: tensile strength 1030 MPa, electrical conductivity 60.1% IACS, and stress relaxation rate of 57.7% at 200℃ / 1000h.
[0137] As shown in Appendix Table 1, based on the performance data of the above embodiments and comparative examples, it can be seen that the beryllium copper alloy prepared by the present invention using a combination process of tensionless pre-aging and three "cold rolling + micro-tension aging" has significant advantages in comprehensive performance compared with the traditional tensionless aging process.
[0138] First, this invention, by precisely controlling the stress range of micro-tension aging, promotes the precipitation of nanoscale strengthening phases while actively driving the slip, climb, and annihilation of mobile dislocations introduced by cold rolling, thereby minimizing the mobile dislocation density. The alloy of this invention exhibits significantly better tensile strength, electrical conductivity, and stress relaxation resistance than traditional tensionless aging processes, with a substantial reduction in stress relaxation rate and simultaneous improvement in strength and electrical conductivity. Second, the stress value during micro-tension aging must be strictly controlled. Too low a stress cannot effectively eliminate mobile dislocations, while too high a stress leads to excessively coarse precipitates and the reactivation and annihilation of fixed dislocations, resulting in a sharp decline in strength and stress relaxation resistance. Therefore, this invention limits the stress within a reasonable range and gradually decreases it, achieving the optimal balance between precipitation strengthening and dislocation elimination. Furthermore, the method of this invention has strong versatility and is applicable to low-beryllium, medium-beryllium, high-beryllium and multi-component beryllium copper alloys (containing Ni, Co, Mg, Zr, Si, etc.). It has achieved excellent comprehensive performance for beryllium copper alloys with different compositions, and the mechanical properties can be further optimized by adjusting the cold rolling deformation amount and aging parameters.
[0139] In summary, this invention significantly outperforms traditional tension-free aging processes in terms of strength, conductivity, and resistance to stress relaxation, and avoids performance degradation caused by over-aging by strictly controlling the micro-tension stress range. This invention can meet the stringent requirements for comprehensive material performance in high-end fields such as aerospace precision relays, 5G high-frequency and high-speed connectors, high-reliability defense electronic systems, and ultra-precision instruments, providing an efficient and controllable preparation method for improving the performance of beryllium copper alloys.
[0140] The above embodiments are merely illustrative examples to clearly illustrate the present invention and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all embodiments here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
[0141] Table 1. Performance Comparison of Examples and Comparative Examples
[0142]
Claims
1. A method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy, characterized in that: The beryllium copper alloy solution billet is pre-aged, and the pre-aged billet is sequentially subjected to one cold rolling, one micro-tension aging, two cold rolling, two micro-tension aging, three cold rolling, and three micro-tension aging. During the first micro-tension aging process, a constant tensile stress F1 is applied along the rolling direction to the alloy plate obtained by the first cold rolling, while the temperature is raised to K1 and held at that temperature. During the secondary micro-tension aging process, a constant tensile stress F2 is applied along the rolling direction to the alloy plate obtained by the secondary cold rolling, while the temperature is raised to K2 and held at that temperature. During the three-stage micro-tension aging process, a constant tensile stress F3 is applied along the rolling direction to the alloy plate obtained by the three-stage cold rolling, while the temperature is raised to K3 and held at that temperature. Where F1>F2>F3, K1>K2>K3.
2. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 1, characterized in that: The process of obtaining the beryllium copper alloy solution billet is as follows: homogenize the beryllium copper alloy ingot to obtain a homogenized billet, hot-roll the homogenized billet to obtain a hot-rolled billet, and then perform solution treatment on the hot-rolled billet to obtain the final product.
3. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 2, characterized in that: The hot rolling temperature is 750-970℃. Before hot rolling, the temperature is held at 750-970℃ for 1-3 hours, and between passes, the temperature is held at 750-970℃ for 15-30 minutes. After hot rolling, the temperature is cooled to room temperature with water. The hot rolling process is carried out in three passes, with a total deformation of 70-85% and a deformation of 35-40%, 20-35%, and 15-30% of the total deformation for each pass, respectively. The solution treatment is carried out under a protective atmosphere, the temperature of the solution treatment is 780~950℃, and the time of the solution treatment is 0.5~4h. After the solution treatment is completed, the solution is quenched with water to room temperature to obtain a solution-treated billet.
4. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 3, characterized in that: When the beryllium mass fraction in the beryllium-copper alloy is ≤0.6 wt%, the solution treatment temperature is 880~950℃ and the solution treatment time is 0.5~4h; when the beryllium mass fraction in the beryllium-copper alloy is >0.6 wt%, the solution treatment temperature is 780~870℃ and the solution treatment time is 0.5~3h.
5. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 1, characterized in that: The pre-aging is carried out under a protective atmosphere, the pre-aging temperature is 280~450℃, the pre-aging time is 0.5~3h, and after the pre-aging is completed, it is cooled to room temperature with water.
6. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 5, characterized in that: When the beryllium mass fraction in the beryllium copper alloy is ≤0.6 wt%, the pre-aging temperature is 400~450℃ and the pre-aging time is 0.5~2h. When the beryllium mass fraction in the beryllium copper alloy is >0.6 wt%, the pre-aging temperature is 280~350℃ and the pre-aging time is 0.5~3h.
7. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 1, characterized in that: The total deformation of the first cold rolling is 50% to 80%, and the first cold rolling is carried out in three passes, with the deformation of each pass being 40% to 50%, 20% to 35%, and 15% to 30% of the total deformation, respectively. The total deformation of the secondary cold rolling is 30% to 60%, and the secondary cold rolling is carried out in three passes, with the deformation of each pass being 40% to 45%, 25% to 35%, and 20% to 35% of the total deformation, respectively. The total deformation of the three cold rolling processes is 30% to 60%, and the three cold rolling processes are carried out in three passes, with the deformation amounts of each pass being 40% to 45%, 25% to 35%, and 20% to 35% of the total deformation, respectively.
8. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 1, characterized in that: F1 is 120-200MPa, F1 is 20-50MPa greater than F2, and F2 is 20-50MPa greater than F3.
9. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 1, characterized in that: K1 is 280~450℃, K1 is 5~50℃ higher than K2, and K2 is 5~50℃ higher than K3.
10. The method for preparing a high-strength, high-stress-relaxation-resistant beryllium copper alloy according to claim 9, characterized in that: When the beryllium mass fraction in the beryllium copper alloy is ≤0.6 wt%, K1 is 400~450℃, and the holding time at K1 is 0.5~2h; when the beryllium mass fraction in the beryllium copper alloy is >0.6 wt%, K1 is 280~350℃, and the holding time at K1 is 0.5~3h.